Reduksi Kemiskinan pada Kabupaten/Kota di Provinsi Sumatera Selatan - Siti Rohima; Liliana Liliana; Aning Kesuma Putri (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2020)
Local Government expenditure is budgeting for all government needs and activities and managed under the authority of provinces, regencies, and municipalities through their respective regional heads. Well-targeted Local Government expenditure optimization has a significant impact on the regional economy. This research aims to determine poverty reduction in regencies/municipalities in South Sumatra Province, Indonesia, by examining the variable’s impact of social assistance expenditure, capital expenditure, and local revenue on poverty. The data used are primary and secondary data obtained from 15 regencies/municipalities in South Sumatra Province during the 2010-2018 periods. The analysis technique uses in this research were Poverty Mapping with Klassen Typology and Multiple Linear Regression (MLR). Using the Klassen typology for poverty mapping in South Sumatra Province obtained four regional classifications (quadrant) based on poverty and economic growth: quadrant I (developed and fast-growing region), quadrant II (developed but depressed region), quadrant III (developing region), and quadrant IV (less developed region). The Klassen typology classification results: quadrant I include Palembang City, quadrant II includes Musi Banyuasin Regency, Muara Enim Regency, Ogan Komering Ilir Regency, and Banyuasin Regency. Quadrant III includes Ogan Komering Ulu Regency, Prabumulih City, and Lubuk Linggau City. Also, quadrant IV includes Lahat Regency, Musi Rawas Regency, Ogan Ilir Regency, Ogan Komering Ulu Timur Regency, Ogan Komering Ulu Selatan Regency, Empat Lawang Regency, and Pagar Alam City. The t-test regression results showed that Social assistance expenditure and local revenue affect poverty reduction, while capital expenditure does not significantly affect poverty reduction. The F-test regression results showed that poverty reduction was affected simultaneously by social assistance expenditure, capital expenditure, and local revenue. Policies in social assistance expenditure and capital expenditure were not well-targeted. The policies expected to reduce poverty are to provide well-targeted social assistance expenditure and capital expenditure.